History in our time - Cannadine, David, 1950- (Yale University Press, 1998)
"Cannadine's subject is nineteenth- and twentieth-century Britain ... [with] subjects as varied as suicide and divorce, patriotism and empire, class and privacy, and ... 'Victorian values.'"--Jacket